2010
DOI: 10.1128/jvi.02176-09
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of α V β 3 and α V β 6 Integrins with Human Parechovirus 1

Abstract: Human parechovirus (HPEV) infections are very common in early childhood and can be severe in neonates. It has been shown that integrins are important for cellular infectivity of HPEV1 through experiments using peptide blocking assays and function-blocking antibodies to ␣ V integrins. The interaction of HPEV1 with ␣ V integrins is presumably mediated by a C-terminal RGD motif in the capsid protein VP1. We characterized the binding of integrins ␣ V ␤ 3 and ␣ V ␤ 6 to HPEV1 by biochemical and structural studies. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
71
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 50 publications
(74 citation statements)
references
References 91 publications
(87 reference statements)
2
71
0
Order By: Relevance
“…Such a role for the RGD motif for HPeV1 has been shown through blocking experiments with RGD-containing peptides, antibodies (Abs), and mutations of the sequence, where deletion of the RGD motif is lethal (12)(13)(14)(15)(16). Studies of the HPeV1 virion in complex with both ␣ V ␤ 3 and ␣ V ␤ 6 integrins confirmed that they have overlapping binding sites on the predicted site of the RGD motif on the capsid surface (6). There are several potential neutralizing mechanisms for antibodies that bind specifically to viral capsid surfaces, e.g., antibodies may neutralize by obstructing a receptor-binding site, cause viral aggregation as a result of interlinking particles, or bind bivalently, preventing uncoating (17)(18)(19).…”
mentioning
confidence: 91%
See 1 more Smart Citation
“…Such a role for the RGD motif for HPeV1 has been shown through blocking experiments with RGD-containing peptides, antibodies (Abs), and mutations of the sequence, where deletion of the RGD motif is lethal (12)(13)(14)(15)(16). Studies of the HPeV1 virion in complex with both ␣ V ␤ 3 and ␣ V ␤ 6 integrins confirmed that they have overlapping binding sites on the predicted site of the RGD motif on the capsid surface (6). There are several potential neutralizing mechanisms for antibodies that bind specifically to viral capsid surfaces, e.g., antibodies may neutralize by obstructing a receptor-binding site, cause viral aggregation as a result of interlinking particles, or bind bivalently, preventing uncoating (17)(18)(19).…”
mentioning
confidence: 91%
“…HPeV infections mainly cause mild gastrointestinal symptoms, although HPeV are also associated with more severe central nervous system symptoms, such as meningitis and neonatal sepsis (2)(3)(4)(5). The HPeV genome is about 7,300 bases in length, enclosed in an icosahedrally symmetric capsid of 60 copies of each of the three capsid proteins VP0, VP3, and VP1 (1,6). HPeV lack the maturation cleavage of the capsid protein VP0 into VP4 and VP2, which is present in most picornaviruses (7).…”
mentioning
confidence: 99%
“…However, the cleavage of VP0 into VP2 and VP4 does not appear in parechoviruses and the manner of how maturation and virus release is achieved for HPeVs remains largely unknown (Stanway et al, 1994). Nonetheless, the external appearance of HPeV particles has proved consistent with the external appearance of other picornaviruses, most closely resembling Foot and Mouth Disease Virus (FMDV) in the Aphthovirus genus as has recently been shown by cryoelectron microscopy and image reconstruction (Seitsonen et al, 2010).…”
Section: Wwwintechopencommentioning
confidence: 85%
“…The hydrophobic pocket is relatively well preserved among EVs and HRVs, resulting in a broad-spectrum anti-enteroviral and -rhinoviral activity of pleconaril. However, the capsid of HPeVs is different Seitsonen et al, 2010), indicating that the hydrophobic pocket differs from that of EVs. Indeed data from our laboratory show that HPeV1 and HPeV3 are resistant against pleconaril in vitro (Wildenbeest et al, 2010).…”
Section: Treatmentmentioning
confidence: 99%
“…The digitized micrographs were processed, and viral particles were picked as previously described (49). The initial models for the viruses at approximately 30-Å resolution were generated using a random model computation method with a subset of 150 far from focus particles (50).…”
Section: Methodsmentioning
confidence: 99%